Low Global Diversity of Candidatus Microthrix, a Troublesome Filamentous Organism in Full-Scale WWTPs - Nierychlo, Marta; Singleton, Caitlin M.; Petriglieri, Francesca; Thomsen, Lisette; Petersen, Jette F.; Peces, Miriam; Kondrotaite, Zivile; Dueholm, Morten S.; Nielsen, Per H. (Frontiers in Microbiology, 2021)
Candidatus Microthrix is one of the most common bulking filamentous microorganisms found in activated sludge wastewater treatment plants (WWTPs) across the globe. One species, Ca. M. parvicella, is frequently observed, but global genus diversity, as well as important aspects of its ecology and physiology, are still unknown. Here, we use the MiDAS ecosystem-specific 16S rRNA gene database in combination with amplicon sequencing of Danish and global WWTPs to investigate Ca. Microthrix spp. diversity, distribution, and factors affecting their global presence. Only two species were abundant across the world confirming low diversity of the genus: the dominant Ca. M. parvicella and an unknown species typically present along with Ca. M. parvicella, although usually in lower abundances. Both species were mostly found in Europe at low-to-moderate temperatures and their growth was favored in municipal WWTPs with advanced process designs. As no isolate is available for the novel species, we propose the name “Candidatus Microthrix subdominans”. Ten high-quality metagenome-assembled genomes recovered from Danish WWTPs, including 6 representing the novel Ca. M. subdominans, demonstrated high genetic similarity between the two species with a likely preference for lipids, a putative capability to reduce nitrate and nitrite, and the potential to store lipids and polyP. Ca. M. subdominans had a potentially more versatile metabolism including additional sugar transporters, higher oxygen tolerance, and the potential to use carbon monoxide as energy source. Newly designed fluorescence in situ hybridization probes revealed similar filamentous morphology for both species. Raman microspectroscopy was used to quantify the in situ levels of intracellular poly-P. Despite the observed similarities in their physiology (both by genomes and in situ), the two species showed different seasonal dynamics in Danish WWTPs through a 13-years survey, possibly indicating occupation of slightly different niches. The genomic information provides the basis for future research into in situ gene expression and regulation, while the new FISH probes provide a useful tool for further characterization in situ. This study is an important step towards understanding the ecology of Ca. Microthrix in WWTPs, which may eventually lead to the optimization of control strategies for its growth in this ecosystem.